Real-Time Perceptual Simulation of Moving Sources: Application to the Leslie Cabinet and 3D Sound Immersion. (3rd July 2008) - Kronland-Martinet, R.; Voinier, T.
Abstract : Perception of moving sound sources obeys different brain processes from those mediating the localization of static sound events. In view of these specificities, a preprocessing model was designed, based on the main perceptual cues involved in the auditory perception of moving sound sources, such as the intensity, timbre, reverberation, and frequency shift processes. This model is the first step toward a more general moving sound source system, including a system of spatialization. Two applications of this model are presented: the simulation of a system involving rotating sources, the Leslie Cabinet and a 3D sound immersion installation based on the sonification of cosmic particles, the Cosmophone .